Factors related to Depression among Agricultural Aging Workers - Saleekul, Sumlee; Kaewboonchoo, Orawan; Tipkanjanaraykha, Kitsanaporn (Journal of The Royal Thai Army Nurses, 2020)
This descriptive study with cross-sectional design aim to examine factors relate to depression of agricultural aging workers. The samples were 364 aging workers. Research instruments include demographic questionnaire, agricultural work stress, interpersonal relationship problems, depression, blood cholinesterase (ChE) level, and digital blood pressure. Data was analyzed using descriptive statistic, Chi-square, and logistic regression. Relationships between personal factors and depression among elderly agriculture workers for male gender were age, education, income, alcohol and cigarette use, high blood pressure, diabetes, and deaths of love ones. Whereas for female were age, education, income, marital status, chronic illness from high blood pressure or diabetes. Deaths of love one has significant relationship with depression of male worker. ChE level were found to have none significant relationship with depression among male and female aging agricultural workers. Logistic regression showed variables related to depression, for male were age, education, income, and illness from high blood pressure or diabetes. For female were age, education, marital status, and deaths of love one, (p<.05).